An All‐Optically Controlled Liquid‐Crystal Plasmonic Metasurface Platform. Issue 11 (23rd September 2020) - Sharma, Mukesh; Ellenbogen, Tal
Abstract: The need for thin active metasurface based elements, opens an exciting research direction toward exploration of various active materials and their control mechanisms. Here, an all‐optical control mechanism of composite metasurfaces is studied, based on rapid laser‐induced thermo‐optical nonlinearities in nematic liquid crystals (NLCs). Specifically, the absorption of photons leads to local heating, which in turn facilitates a nematic‐to‐isotropic (N – I) phase transition of a twisted‐NLC (TNLC) layer that is sandwiched between an indium tin oxide (ITO) coated glass plate and the metasurface. This mechanism is used to experimentally demonstrate all‐optically switchable plasmonic metasurface color tag. The dependence of the switching on the laser power and the dynamic response of the device are characterized. Experimental results show that the pump beam power significantly affects the switching time, which can be further reduced by thermal management of the design. Such switching mechanisms have great potential in all‐optically controlled systems and can be applied to realize additional active and multifunctional optical devices at nanoscale. Abstract : All‐optically controlled liquid‐crystal (LC) plasmonic metasurface platform based thermo‐optical nematic‐to‐isotropic phase transition in a twisted nematic‐LC (TNLC) layer, is demonstrated. By employing this control mechanism, an all‐optically switchable plasmonic metasurface color tag (TAU) is experimentally demonstrated. The dependence of the switching on the laser power and the dynamic response of the device are characterized.